The limits to wage-led growth in a low-income economy - Arslan Razmi (University of Massachusetts, Department of Economics, 2015)
Neo-Kaleckian literature has actively debated whether growth is wage- or profit-led in capitalist economies. However, existing studies tend to ignore the non-tradable sector and heterogeneity within the tradable sector. This paper shows that incorporating these features renders wage-led growth in an open developing economy unfeasible in the traditional (Kaleckian) sense of the term. This result - which follows even if one sets aside the competitiveness considerations generally seen as impeding such growth - occurs due to the presence of a homogeneous goods-producing tradable sector that sets the ceiling to steady state growth. A corollary, in light of findings from the "new new trade theory" literature, is that increasing South-South trade may tend to narrow room for wage-led growth regardless of the other desirable effects of higher wages.
Keywords: F43; F66; O41; F63; E12; 330; Wage-led growth; non-tradables; neo-Kaleckian models; development; output heterogeneity